The Role of Digital Culture in Mediating Transformational Leadership on Employee Performance - Rivan Sumara, Andry; Sobandi, A.; Sojanah, Janah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Leadership is one of the factors that influence the business process of an organization. The current era of digitalization is developing rapidly and the leadership factor is still a vital part of changing and improving digital business processes, one of which is in the government sector. This study will examine digital culture in mediating between transformational leadership and employee performance. The study was conducted using quantitative methods. The location of the study was in the work unit of the Human Resources Development Agency of the Ministry of Communication and Informatics. The results of the study indicate that transformational leadership has a strong influence on digital culture and digital culture strongly mediates between transformational leadership and employee performance, but transformational leadership has a weak influence on employee performance.